Il declino di un’illusione. Un dibattito sulla psichiatria contemporanea - Nella Lo Cascio; Francesca Fagioli (Il sogno della farfalla, 2013)
This paper discusses an article written by Dr. Marcia Angell and published in two issues “The New York Review of Books” in July 2011. The first part of it focuses on the books by the psychologist Irving Kirsch and the journalist Robert Whitaker, while in the second part, M. Angell discusses the Diagnostic and statistical manual of mental disorders, and its influence worldwide. Her article − which also examines Unhinged, a book by Daniel Carlat, a psychiatrist who provides a disillusioned view of his profession − has raised a vivid debate among psychiatrists. Some psychiatrists regretted that a more balanced approach towards modern psychiatry had not been taken. Others argued that even if we do not understand the mechanism governing mental illness, drugs are nevertheless effective. This paper highlights the importance of Angell's article which focuses on the state of contemporary psychiatry, seen as far from being effective. It also points out the failure of the DSM oriented approach and our reliance on psychoactive drugs which tends to close off other options. This view could lead psychiatrists to study different treatments which take environmental factors into consideration, such as psychotherapy.